Performance of base hydrolysis methods in extracting bound lipids from plant material, soils, and sediments. (November 2017) - Angst, Gerrit; Cajthaml, Tomáš; Angst, Šárka; Mueller, Kevin E.; Kögel-Knabner, Ingrid; Beggel, Sebastian; Kriegs, Stefanie; Mueller, Carsten W.
Graphical abstract: Highlights: Reflux, ultrasound, and 'bomb' methods for extraction of bound lipids were compared. The reflux method gave consistently higher yields independent of extracted material. Yield of certain lipids, including cutin acids, may be sensitive to the method used. Abstract: Base hydrolysis methods are widely used to extract bound lipid biomarkers such as cutin and suberin from plant material, soils, and sediments. However, non-uniform treatments among studies hamper their comparability, and information on differences between commonly used saponification methods does not exist. The aim of the present study was to compare frequently used base hydrolysis methods and evaluate their performance in extracting bound lipids from common European forest and agricultural plant species ( Fagus sylvatica L. and Zea mays L.), and corresponding soils and sediments. We compared extraction in Teflon-lined bombs, ultrasound assisted extraction, and extraction with reflux in quintuplicate for each plant, soil, and sediment material. The reflux method gave consistently higher yields of bound lipids as compared to the other two methods, while requiring the same amount of time and solvent and featuring lower standard errors. Some lipids, including common building blocks of cutin and, to a lesser extent, suberin, were more efficiently extracted by the reflux method than others, indicating that source assignment of organic matter in soils and sediments via biomarkers might be sensitive to the employed method. Although the other extraction methods may perform similarly under different conditions, such as other sample matrices, extraction conditions of the reflux method may potentially be more easily controlled across replicates and laboratories as compared to the bomb or ultrasound methods. Thus, the use of reflux methods ensures meaningful yields of hydrolysable lipids while providing high reproducibility.